2015
DOI: 10.1002/jor.22872
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic angles in hallux valgus: Comparison between protractor and iPhone measurements

Abstract: Radiographic angles are used to assess the severity of hallux valgus deformity, make preoperative plans, evaluate outcomes after surgery, and compare results between different methods. Traditionally, hallux valgus angle (HVA) has been measured by using a protractor and a marker pen with hardcopy radiographs. The main objective of this study is to compare HVA measurements performed using a smartphone and a traditional protractor. The secondary objective was to compare the time taken between those two methods. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Condon et al 8 and Meng et al 14 confirmed the high intra- and interobserver reliability for the measurement of the IM angle; however, they concluded that reliability can be improved using a sound technique and repeating the measurements at least twice. Hujazia et al 15 assessed the reliability of measuring HVI using a computerized measurement technique.…”
Section: Discussionmentioning
confidence: 98%
“…Condon et al 8 and Meng et al 14 confirmed the high intra- and interobserver reliability for the measurement of the IM angle; however, they concluded that reliability can be improved using a sound technique and repeating the measurements at least twice. Hujazia et al 15 assessed the reliability of measuring HVI using a computerized measurement technique.…”
Section: Discussionmentioning
confidence: 98%
“…The Hallux Angles software had been proven to be an accurate and reproducible method compared with the conventional PACS system [ 11 ]. Yang et al found that the Tiltmeter software in iPhone is superior to PACS in measuring time but with the same accuracy [ 13 ]. Mattos et al even showed that one iPhone app named iPinPoint could even be operated by non-experienced observers, which means patients may be able to self-screening such deformities [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, computer-assisted image analysis software and smartphone applications have become widespread in daily use, in which the Picture archiving and communication systems (PACS) were considered as the gold standard. Some applications of iPhone have been developed and described to measure the angles of hallux valgus in previous researches [ 10 – 13 ]. In our previous study, we introduced a brand-new method of measuring the hallux valgus angles conveniently and rapidly with the intrinsic photograph-editing function of Android smartphones [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The iPhone Hallux Angles app was proven to be a reliable method to measure HVA and IMA when compared to PACS [ 6 ]. The Tiltmeter software for iPhones is precise and less time-consuming than traditional measurements with protractors [ 7 ]. One app named iPinPoint is suggested to be reliable for the measurement of HVA and IMA, even for nonexperienced users [ 8 ].…”
Section: Discussionmentioning
confidence: 99%